Near-Field Stationary Sample Terahertz Spectroscopic Polarimetry for Biomolecular Structural Dynamics Determination - Deng, Y.; McKinney, J. A.; George, D. K.; Niessen, K. A.; Sharma, A.; Markelz, A.G. (ACS Photonics, 2021)
THz polarimetry on environmentally sensitive and microscopic samples can provide unique insight into underlying mechanisms of complex phenomena. For example, near-field THz anisotropic absorption successfully isolated protein structural vibrations which are connected to biological function. However, to determine how these vibrations impact function requires high throughput measurements of these complex systems, which is challenged by the need for near field detection, sample environmental control and full polarization variation. Stationary sample anisotropic terahertz spectroscopy (SSATS) and near-field stationary sample anisotropic terahertz microscopy (SSATM) have been proposed using synchronous control of THz and electro optic probe polarizations along an iso-response curve. Here we realize these techniques through robust control and calibration of the THz and NIR polarization states. Both methods rapidly measure the linear dichroism in the far field and near field. Validation measurements using standard birefringent sucrose single crystals found the crystal orientation can be determined by scanning the reference polarization and the synchronous pump–probe polarization settings can be optimized to eliminate artifacts. SSATM is then used to determine spectral reproducibility and dehydration effects for a series of chicken egg white lysozyme samples. Reproducible anisotropic absorbance bands are found at about 30, 44, 55, and 62 cm–1. These bands initially sharpen with slow dehydration, similar to the increase in resolution achieved in X-ray crystallographic protein structure determination. The SSATM technique confirms the reliability of anisotropic absorption characterization of protein intramolecular vibrations and opens an avenue for rapid determination of how these long-range dynamics affect biological function.

Phonon Kinetics of Fructose at the Melting Transition - A. Davie; F. Vandrevala; S. Dampf; Y. Deng; D. K. George; E. D. Sylvester; T. Korter; E. Einarsson; J. B. Benedict; A. G. Markelz (J. Phys. Chem. C, 2021)
Terahertz time domain spectroscopy (THz TDS) is used to measure the melting kinetics of fructose molecular crystals. Combining single-crystal anisotropy measurements with density functional calculations, we assign the phonon frequencies and interrogate how specific phonons behave with melting. While nearly all the low-frequency phonons continuously red-shift with heating and melting, the lowest-energy phonon polarized along the c-axis blue-shifts at the melting temperature, suggesting an initial structural change immediately before melting. We find that the kinetics follow a 3D growth model with large activation energies, consistent with previous differential scanning calorimetry (DSC) measurements. The large activation energies indicate that multiple H-bonds must break collectively for the transition. The results suggest the generality of the kinetics for molecular crystals and that THz TDS with picosecond resolution could be used to measure ultrafast kinetics.

Evidence of Intramolecular Structural Stabilization in Light Activated State of Orange Carotenoid Protein - McKinney, J. A.; Sharma, A.; Crossen, K.; Deng, Y.; George, D. K.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. G. (Biophysical Journal, 2020)
Orange carotenoid protein (OCP) controls efficiency of the light harvesting antenna, the phycobilisome (PBS), in diverse cyanobacteria and prevents oxidative damage. It is the only known photoactive protein that uses a carotenoid, canthaxanthin, as its chromophore. The structure of OCP consists of two globular domains, connected by an unstructured loop, that forms a hydrophobic pocket for the carotenoid. In low light, canthaxanthin bound OCP is inactive and appears orange. Illumination by strong light results in an active state that interacts with the PBS to induce fluorescence quenching, a red appearance and conformational changes that include a 12Å shift by canthaxanthin into the N-terminal domain. Terahertz (THz) dynamical transition measurements and anisotropic terahertz microscopy are used to measure the intramolecular structural dynamics in the inactive and active states, which can be induced by photoexcitation or chaotropic salts. The measurements indicate that the active state has a decrease in structural flexibility, which may be related to enhanced interactions with the PBS.
ISI Document Delivery No.: KK8YX Times Cited: 0 Cited Reference Count: 0 McKinney, Jeffrey A. Sharma, Akansha Crossen, Kimberly Deng, Yanting George, Deepu K. Lechno-Yossef, Sigal Kerfeld, Cheryl Markelz, Andrea G. 64th Annual Meeting of the Biophysical-Society Feb 15-19, 2020 San Diego, CA Biophys Soc NSFNational Science Foundation (NSF) [DBI 1556359, MCB 1616529]; DOEUnited States Department of Energy (DOE) [DE-SC0016317]; NIH STTRUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USA [R41 GM125486] This work is supported by NSF grants DBI 1556359 and MCB 1616529, DOE grant DE-SC0016317 and NIH STTR R41 GM125486. 1 2 Cell press Cambridge 1542-0086
Keywords: Biophysics

Linear dichroism infrared resonance in overdoped, underdoped, and optimally doped cuprate superconductors - Mukherjee, A.; Seo, J.; Arik, M. M.; Zhang, H.; Zhang, C. C.; Kirzhner, T.; George, D. K.; Markelz, A. G.; Armitage, N. P.; Koren, G.; Wei, J. Y. T.; Cerne, J. (Physical Review B, 2020)
By measuring the polarization changes in terahertz, infrared, and visible radiation over an extended energy range (3-2330 meV), we observe symmetry breaking in cuprate high-temperature superconductors over wide energy, doping, and temperature ranges. We measure the polarization rotation (Re[theta(F)]) and ellipticity (Im[theta(F)]) of transmitted radiation through thin films as the sample is rotated. We observe a twofold rotational symmetry in theta(F), which is associated with linear dichroism (LD) and occurs when electromagnetic radiation polarized along one direction is absorbed more strongly than radiation polarized in the perpendicular direction. Such polarization anisotropies can be generally associated with symmetry breakings. We measure the amplitude of the LD signal and study its temperature, energy, and doping dependence. The LD signal shows a resonant behavior with a peak in the few hundred meV range, which is coincident with the midinfrared optical feature that has been associated with the formation of the pseudogap state. The strongest LD signal is found in underdoped films, although it is also observed in optimally and overdoped samples. The LD signal is consistent with an electronic nematic order which is decoupled from the crystallographic axes as well as novel magnetoelectric effects.
ISI Document Delivery No.: NE5GO Times Cited: 0 Cited Reference Count: 30 Cited References: Acbas G, 2009, PHYS REV LETT, V103, DOI 10.1103/PhysRevLett.103.137201 Armitage NP, 2014, PHYS REV B, V90, DOI 10.1103/PhysRevB.90.035135 Arpaia R, 2018, PHY REV MATER, V2, DOI 10.1103/PhysRevMaterials.2.024804 Basov DN, 2005, REV MOD PHYS, V77, P721, DOI 10.1103/RevModPhys.77.721 Blumberg G, 1996, PHYS REV B, V53, P11930, DOI 10.1103/PhysRevB.53.R11930 Cerne J, 2000, PHYS REV LETT, V84, P3418, DOI 10.1103/PhysRevLett.84.3418 Fauque B, 2006, PHYS REV LETT, V96, DOI 10.1103/PhysRevLett.96.197001 Fridman I, 2011, PHYS REV B, V84, DOI 10.1103/PhysRevB.84.104522 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Halperin B. I., 1991, SPRINGER P PHYS, V60, P439 Humlicek J, 2000, PHYS REV B, V61, P14554, DOI 10.1103/PhysRevB.61.14554 KOREN G, 1989, APPL PHYS LETT, V54, P1054, DOI 10.1063/1.101559 Koren G, 2016, PHYS REV B, V94, DOI 10.1103/PhysRevB.94.174515 Lubashevsky Y, 2014, PHYS REV LETT, V112, DOI 10.1103/PhysRevLett.112.147001 Mukherjee A, 2019, PHYS REV B, V99, DOI 10.1103/PhysRevB.99.085440 Nie LM, 2014, P NATL ACAD SCI USA, V111, P7980, DOI 10.1073/pnas.1406019111 Orenstein J, 2011, PHYS REV LETT, V107, DOI 10.1103/PhysRevLett.107.067002 PISAREV RV, 1991, PHASE TRANSIT, V37, P63, DOI 10.1080/01411599108203448 Simon ME, 2002, PHYS REV LETT, V89, DOI 10.1103/PhysRevLett.89.247003 TROFIMOV IE, 1994, APPL PHYS LETT, V65, P2481, DOI 10.1063/1.112671 Varma CM, 2014, EPL-EUROPHYS LETT, V106, DOI 10.1209/0295-5075/106/27001 Varma CM, 1997, PHYS REV B, V55, P14554, DOI 10.1103/PhysRevB.55.14554 Wu J, 2017, NATURE, V547, P432, DOI 10.1038/nature23290 Xia J, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.127002 Yakes MK, 2010, NANO LETT, V10, P1559, DOI 10.1021/nl9035302 Yakovenko VM, 2015, PHYSICA B, V460, P159, DOI 10.1016/j.physb.2014.11.060 Zhang H, 2018, PHYS REV MATER, V2, DOI 10.1103/PhysRevMaterials.2.033803 Zhang J, 2018, SCI ADV, V4, DOI 10.1126/sciadv.aao5235 Zhao L, 2017, NAT PHYS, V13, P250, DOI [10.1038/nphys3962, 10.1038/NPHYS3962] Zhao L., 2018, ENCY MODERN OPTICS, P207 Mukherjee, A. Seo, J. Arik, M. M. Zhang, H. Zhang, C. C. Kirzhner, T. George, D. K. Markelz, A. G. Armitage, N. P. Koren, G. Wei, J. Y. T. Cerne, J. NSF-DMR GrantNational Science Foundation (NSF) [1410599]; NSFNational Science Foundation (NSF) [MCB 1616529, DMR 1905519]; DOEUnited States Department of Energy (DOE) [DE-SC0016317]; NSERCNatural Sciences and Engineering Research Council of Canada (NSERC); CFI-OITCanada Foundation for Innovation; Canadian Institute for Advanced ResearchCanadian Institute for Advanced Research (CIFAR) We are indebted to D. Hsieh, S. A. Kivelson, C. M. Varma, and L. Zhao for helpful discussions. We gratefully acknowledge support from NSF-DMR Grant No. 1410599 (J.C.). A.G.M. and D.K.G. were supported by NSF Grant No. MCB 1616529 and DOE Grant No. DE-SC0016317. Work in Toronto was supported by NSERC, CFI-OIT, and the Canadian Institute for Advanced Research. J.Y.T.W. thanks Kejun Xu for laboratory assistance in Toronto. N.P.A. was supported by NSF Grant No. DMR 1905519. 9 Amer physical soc College pk 2469-9969
Keywords: Materials Science; Physics

Is the Protein Dynamical Transition useful? - Sharma, A.; George, D. K.; Crossen, K.; McKinney, J.; Kerfeld, C.; Markelz, A. (Biophysical Journal, 2020)

Stabilization of Terahertz Vibrational Modes in Illuminated Orange Carotenoid Protein Crystals - McKinney, J.; Sharma, A.; Deng, Y.; George, D.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. (2020 45th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz), 2020)
Orange carotenoid protein (OCP) controls efficiency of the phycobilisome (PBS), the light harvesting antenna in cyanobacteria, to prevent oxidative damage. The OCP switches from resting state to photo protective state with intense blue light illumination. Questions persist as to why OCPR interaction increases with the PBS over that with the OCPO. Here we examine the role of long-range intramolecular vibrations within OCP. Using Stationary Sample Anisotropic Terahertz Microscopy (SSATM) we measure changes in the intramolecular vibrations with photo switching. We report the first observation of switching in the intramolecular vibrations with photoexcitation. Results suggest that there is a stiffening of the molecule in the photo protective state. This increase in structural stability may enhance the interaction with the PBS change in OCP interaction with PBS. In low light, carotenoid bound OCP appears orange (OCP o ) and is inactive. Illumination by strong light converts OCP to the active, red (OCPR) state, which interacts with the PBS. A comparison of anisotropic THz microscopy measurements of dark adapted (OCP o ) and illuminated OCP crystals indicate differences in their vibrational modes that may be important for OCP-PBS interactions.

Anisotropic Terahertz Microscopy of Protein Collective Vibrations: Crystal Symmetry and Hydration Dependence - McKinney, J.; Deng, Y. T.; Sharma, A.; George, D. K.; Markelz, A. G. (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
A stationary sample anisotropic terahertz microscopy technique is used to characterize the intramolecular vibrations for lysozyme. Tetragonal and triclinic crystals are compared. We find excellent reproducibility within a single crystal symmetry group. Several resonant bands are present for both symmetry groups, indicating they originate with the intramolecular vibrations and not crystal lattice phonons. Bands become more pronounced and higher frequency resonant bands begin to emerge with slight dehydration.
ISI Document Delivery No.: BQ4OX Times Cited: 0 Cited Reference Count: 4 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Legrand L, 2002, ACTA CRYSTALLOGR D, V58, P1564, DOI 10.1107/S0907444902014403 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 Niessen KA, 2017, BIOPHYS J, V112, P933, DOI 10.1016/j.bpj.2016.12.049 McKinney, Jeffrey Deng, Yanting Sharma, Akansha George, D. K. Markelz, A. G. Irmmw-thz Proceedings Paper 44th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Sep 01-06, 2019 Paris, FRANCE Lytid, TYDEX, Swiss Terahertz, Fondat Maison Chimie, CNRS, Lab Physique ENS, Li2S, LUNA, MenloSystems, ENS, PSL Univ Paris, FYLA, ADVANTEST, Springer Nature, Soc Francaise Physique, Sorbonne Univ, Int Soc Infrared Millimeter & Terahertz Waves, IEEE, GDR NANO THz MIR NSFNational Science Foundation (NSF) [DBI 1556359, MCB 1616529]; DOEUnited States Department of Energy (DOE) [DE-SC0016317]; NIHUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USA [STTR R41 GM125486] This work is supported by NSF grants DBI 1556359 and MCB 1616529, DOE grant DE-SC0016317 and NIH STTR R41 GM125486. 345 e 47th st, new york, ny 10017 usa 2162-2027

Blue Shift of a Molecular Crystal Phonon at the Solid to Liquid Phase Transition - Davie, Alex; Vandrevala, Farah; Deng, Yanting; George, D.; Sylvester, Eric D.; Korter, T.; Einarsson, E.; Benedict, Jason B.; Markelz, Andrea (Bulletin of the American Physical Society, 2019)

Protein and RNA dynamical fingerprinting - Niessen, Katherine A; Xu, Mengyang; George, Deepu K; Chen, Michael C; Ferré-D’Amaré, Adrian R; Snell, Edward H; Cody, Vivian; Pace, James; Schmidt, Marius; Markelz, Andrea G (Nature communications, 2019)

Stationary Sample Anisotropic THz Spectroscopy using Discretely Tunable THz Sources - LaFave, T., Jr.; George, D. K.; Markelz, A. G.; McNee, Ian; Kozlov, Vladimir; Schunemann, Peter (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
We demonstrate anisotropic THz spectroscopy of sucrose using newly developed compact discretely tunable THz sources for turn-key spectroscopic systems.
Irmmw-thz 44th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Sep 01-06, 2019 Paris, FRANCE Lytid; TYDEX; Swiss Terahertz; Fondat Maison Chimie; CNRS, Lab Physique ENS; Li2S; LUNA; MenloSystems; ENS; PSL Univ Paris; FYLA; ADVANTEST; Springer Nature; Soc Francaise Physique; Sorbonne Univ; Int Soc Infrared Millimeter & Terahertz Waves; IEEE; GDR NANO THz MIR 2162-2027

Tunable Compact Narrow Band THz Sources for Frequency Domain THz Anisotropic Spectroscopy - George, D. K.; LaFave, T. J.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (Conference on Next-Generation Spectroscopic Technologies XII, 2019)
We demonstrate frequency domain THz anisotropy signature detection for protein crystal models using newly developed compact tunable narrow band THz sources based on Orientation Patterned Gallium Phosphide for turn-key spectroscopic systems.
ISI Document Delivery No.: BN5PJ Times Cited: 0 Cited Reference Count: 17 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Chen JY, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2748852 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Lee Y. S., 2006, APPL PHYS LETT, V89 Lee YS, 2000, APPL PHYS LETT, V76, P2505, DOI 10.1063/1.126390 Lin A., 2013, ANTIPHASE DOMAIN ANN Niessen K. A., BIOPHYSICAL J, V112, P933 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 PARSONS DF, 1971, APPL OPTICS, V10, P1683 Singh R., 2013, PHYSICS Strachan CJ, 2005, J PHARM SCI-US, V94, P837, DOI 10.1002/jps.20281 Tassev V., 2013, SPIE LASE, V9 Tekavec P., 2017, FRONTIERS OPTICS 201 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Walther M, 2003, CHEM PHYS, V288, P261, DOI 10.1016/S0301-0104(03)00031-4 Zeitler JA, 2009, EUR J PHARM BIOPHARM, V71, P2, DOI 10.1016/j.ejpb.2008.08.012 George, D. K. LaFave, T. J. Markelz, A. G. Mcnee, Ian Tekavec, Patrick Kozlov, Vladimir Schunemann, Peter LaFave, Tim/0000-0003-2925-8657 NATIONAL INSTITUTE OF GENERAL MEDICAL SCIENCESUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R41GM125486] Funding Source: NIH RePORTER; NIGMS NIH HHSUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R41 GM125486] Funding Source: Medline 0277-786x 1098311
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

Tunable narrow band sources for anisotropic THz spectroscopy - George, D. K.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P.; Markelz, A. G. (APS S23-002, 2019)

Tunable narrowband THz generation in orientation patterned gallium phosphide for THz anisotropy identification - McNee, I.; Tekavec, P.; Kozlov, V.; Markelz, A. G.; George, D. K.; Schunemann, P. (Nonlinear Frequency Generation and Conversion: Materials and Devices Xviii, 2019)
We demonstrate tunable narrowband THz generation by optical rectification of a femtosecond pulse in Orientation Patterned Gallium Phosphide. Center frequencies of 0.9 - 3.8 THz with average power up to 15 mu W were achieved using a 1.064 mu m fiber laser for the pump laser. Biomolecular characterization for an early application of this system is also shown in this work by anisotropic spectroscopic signature detection of molecular crystals in the THz region.
ISI Document Delivery No.: BM9XB Times Cited: 2 Cited Reference Count: 8 Cited References: Fejer M. M., 2013, ANTIPHASE DOMAIN ANN, P258 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Lee YS, 2000, APPL PHYS LETT, V76, P2505, DOI 10.1063/1.126390 Niessen K. A., BIOPHYSICAL J, V112, P933 PARSONS DF, 1971, APPL OPTICS, V10, P1683 Singh R., 2013, MODULATED ORIENTATIO Tassev V., 2013, SPIE LASE, P9 Tekavec P., 2017, FRONTIERS OPTICS 201 McNee, Ian Tekavec, Patrick Kozlov, Vladimir Markelz, A. G. George, D. K. Schunemann, Peter Proceedings Paper Conference on Nonlinear Frequency Generation and Conversion - Materials and Devices XVIII Feb 05-07, 2019 San Francisco, CA Spie 1000 20th st, po box 10, bellingham, wa 98227-0010 usa 0277-786x Unsp 1090218
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

Measuring Protein Intramolecular Dynamics with Terahertz Light: Functional Changes and Relevance to Biology - Xu, M.; Deng, Y.; Luck, C.; Sharma, A.; Markelz, A. (APS 2018, 2018)

THz Anisotropy Identification using Tunable Compact Narrow Band THz Sources - George, D. K.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (2018 43rd International Conference on Infrared, Millimeter, and Terahertz Waves, 2018)
We demonstrate THz anisotropy signature determination of a protein crystal model using newly developed compact tunable narrow band THz sources for turn-key spectroscopic systems for the bio molecular community.
ISI Document Delivery No.: BL3GO Times Cited: 0 Cited Reference Count: 6 Cited References: Dhillon SS, 2017, J PHYS D APPL PHYS, V50, DOI 10.1088/1361-6463/50/4/043001 Lee YS, 2000, APPL PHYS LETT, V76, P2505, DOI 10.1063/1.126390 Lin A., 2013, ANTIPHASE DOMAIN ANN, P258 Niessen KA, 2017, BIOPHYS J, V112, P933, DOI 10.1016/j.bpj.2016.12.049 Tassev V., 2013, SPIE LASE, P9 Tekavec P., 2017, FRONTIERS OPTICS 201 George, D. K. Markelz, A. G. Mcnee, Ian Tekavec, Patrick Kozlov, Vladimir Schunemann, Peter Irmmw-thz Proceedings Paper 43rd International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Sep 09-14, 2018 Nagoya, JAPAN IEEE Microwave Theory & Tech Soc, TeraTech, JSPS, JSIR, Japan Soc Appl Phys, IEEJ, CSJ, AIP, APL Photon, AIP, Journal Appl Phys, EiC, SPSJ, Terahertz Syst Consortium, AICHI, Nagoya Convent & Visitors Bur, ADVANTEST CORP, AmTechs Corp, Menlo Systems GmbH, Nippo Precigion Co Ltd, TeraMetrix LLC Div Luna, ATN Japan LTD, DAHENG NEW EPOCH TECHNOL INC, FEMTO Dev Inc, KYOWA FINTECH Co Ltd, Spectra Design Ltd, TeraView Ltd, TYDEX LLC, Virginia Diodes Inc, PNP, Tydex Res & Ind Opt, Femtowave, Kyowa Fine Tech Co Ltd, Daheng Opt 345 e 47th st, new york, ny 10017 usa 2162-2027

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
ISI Document Delivery No.: EI0HL Times Cited: 541 Cited Reference Count: 209 Cited References: Adam AJL, 2011, J INFRARED MILLIM TE, V32, P976, DOI 10.1007/s10762-011-9809-2 Ahmed SS, 2012, IEEE MICROW MAG, V13, P26, DOI 10.1109/MMM.2012.2205772 Alliance N., 2015, CISC VIS NETW IND GL, P1 [Anonymous], 2013, 178512012 IEEE [Anonymous], 2014, IEEE T ELECT DEVICES, V61 [Anonymous], 2012, 178522016 IEEE [Anonymous], 2015, P17852 IEEE Appleby R, 2015, P SOC PHOTO-OPT INS, V9462 Arnone DD, 1999, PROC SPIE, V3828, P209, DOI 10.1117/12.361037 Ashworth PC, 2009, OPT EXPRESS, V17, P12444, DOI 10.1364/OE.17.012444 AUSTON DH, 1988, IEEE J QUANTUM ELECT, V24, P184, DOI 10.1109/3.114 Barbieri S, 2011, NAT PHOTONICS, V5, P306, DOI [10.1038/NPHOTON.2011.49, 10.1038/nphoton.2011.49] Barker RJ., 2005, MODERN MICROWAVE MIL Basov DN, 2011, REV MOD PHYS, V83, P471, DOI 10.1103/RevModPhys.83.471 Bauwens M. F., 2014, P IEEEMTT S INT MICR, P1, DOI [10.1109/MWSYM.2014.68486 07, DOI 10.1109/MWSYM.2014.6848607] Beard MC, 2002, NANO LETT, V2, P983, DOI 10.1021/nl0256210 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Bechtel HA, 2014, P NATL ACAD SCI USA, V111, P7191, DOI 10.1073/pnas.1400502111 Belkin MA, 2008, OPT EXPRESS, V16, P3242, DOI 10.1364/OE.16.003242 Belkin MA, 2015, PHYS SCRIPTA, V90, DOI 10.1088/0031-8949/90/11/118002 Bell R., 2012, INTRO FOURIER TRANSF Berry CW, 2013, NAT COMMUN, V4, DOI 10.1038/ncomms2638 Blanchard F, 2011, OPT EXPRESS, V19, P8277, DOI 10.1364/OE.19.008277 Blau J, 2013, P FREE EL LAS FEL 20, P486 Booske JH, 2011, IEEE T THZ SCI TECHN, V1, P54, DOI 10.1109/TTHZ.2011.2151610 Booske JH, 2008, PHYS PLASMAS, V15, DOI 10.1063/1.2838240 Boppel S, 2012, 2012 IEEE 12TH TOPICAL MEETING ON SILICON MONOLITHIC INTEGRATED CIRCUITS IN RF SYSTEMS (SIRF), P77, DOI 10.1109/SiRF.2012.6160142 Burghoff D, 2014, NAT PHOTONICS, V8, P462, DOI 10.1038/nphoton.2014.85 Busch SF, 2014, J INFRARED MILLIM TE, V35, P993, DOI 10.1007/s10762-014-0113-9 Byrne MB, 2011, APPL PHYS LETT, V98, DOI 10.1063/1.3579258 Carr GL, 2002, NATURE, V420, P153, DOI 10.1038/nature01175 Carranza IE, 2015, IEEE T THZ SCI TECHN, V5, P892, DOI 10.1109/TTHZ.2015.2463673 Castro-Camus E, 2007, OPT EXPRESS, V15, P7047, DOI 10.1364/OE.15.007047 Chan WL, 2007, REP PROG PHYS, V70, P1325, DOI 10.1088/0034-4885/70/8/R02 Chattopadhyay G, 2011, IEEE T THZ SCI TECHN, V1, P33, DOI 10.1109/TTHZ.2011.2159561 Chen HT, 2003, APPL PHYS LETT, V83, P3009, DOI 10.1063/1.1616668 Chen JN, 2012, NATURE, V487, P77, DOI 10.1038/nature11254 Cocker T L, 2016, J PHYS D, V16, P1421 Cocker TL, 2013, NAT PHOTONICS, V7, P620, DOI [10.1038/NPHOTON.2013.151, 10.1038/nphoton.2013.151] Coleman B, 2001, Issue Brief (Public Policy Inst (Am Assoc Retired Pers)), P1 Cooper KB, 2014, IEEE MICROW MAG, V15, P51, DOI 10.1109/MMM.2014.2356092 Cruz F C, 2007, C MICR OPT Cunningham J, 2010, ELECTRON LETT, V46, pS34, DOI 10.1049/el.2010.3317 Dean P, 2011, OPT LETT, V36, P2587, DOI 10.1364/OL.36.002587 Dietz RJB, 2014, OPT LETT, V39, P6482, DOI 10.1364/OL.39.006482 Dietz RJB, 2014, OPT EXPRESS, V22, P19411, DOI 10.1364/OE.22.019411 Dobrovolsky V, 2007, SEMICOND SCI TECH, V22, P103, DOI 10.1088/0268-1242/22/2/017 Ducournau G, 2014, IEEE T THZ SCI TECHN, V4, P328, DOI 10.1109/TTHZ.2014.2309006 Dunsmore J.P., 2012, HDB MICROWAVE COMPON Duvillaret L, 1999, APPL OPTICS, V38, P409, DOI 10.1364/AO.38.000409 Eisele M, 2014, NAT PHOTONICS, V8, P841, DOI [10.1038/nphoton.2014.225, 10.1038/NPHOTON.2014.225] Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 Fathololoumi S, 2012, OPT EXPRESS, V20, P3866, DOI 10.1364/OE.20.003866 Fausti D, 2011, SCIENCE, V331, P189, DOI 10.1126/science.1197294 Federici J, 2010, J APPL PHYS, V107, DOI 10.1063/1.3386413 Fei Z, 2012, NATURE, V487, P82, DOI 10.1038/nature11253 FETTERMAN HR, 1974, APPL PHYS LETT, V24, P70, DOI 10.1063/1.1655098 Freeman JR, 2013, OPT EXPRESS, V21, P16162, DOI 10.1364/OE.21.016162 Frisk U, 2003, ASTRON ASTROPHYS, V402, pL27, DOI 10.1051/0004-6361:20030335 Garet F, 2014, APPL PHYS LETT, V105, DOI 10.1063/1.4890732 Gavrilov NG, 2007, NUCL INSTRUM METH A, V575, P54, DOI 10.1016/j.nima.2007.01.023 Gensch M., 2013, P 35 INT FREE EL LAS, P474 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Giliberti V, 2013, APPL PHYS LETT, V103, DOI 10.1063/1.4819734 Grant J, 2013, LASER PHOTONICS REV, V7, P1043, DOI 10.1002/lpor.201300087 Green B, 2016, SCI REP-UK, V6, DOI 10.1038/srep22256 Griffith P.R., 2007, FOURIER TRANSFORM IN GRISCHKOWSKY D, 1990, J OPT SOC AM B, V7, P2006, DOI 10.1364/JOSAB.7.002006 Gruene P, 2008, SCIENCE, V321, P674, DOI 10.1126/science.1161166 Han NR, 2014, OPT LETT, V39, P3480, DOI 10.1364/OL.39.003480 Han RN, 2013, IEEE J SOLID-ST CIRC, V48, P2296, DOI 10.1109/JSSC.2013.2269856 Hanham SM, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4927242 Hassel J, 2015, PROC SPIE, V9651, DOI 10.1117/12.2197522 Hauri CP, 2011, APPL PHYS LETT, V99, DOI 10.1063/1.3655331 He W, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4932099 Hebling J, 2002, OPT EXPRESS, V10, P1161, DOI 10.1364/OE.10.001161 Heinz E, 2015, J INFRARED MILLIM TE, V36, P879, DOI 10.1007/s10762-015-0170-8 Henry SC, 2012, OPT ENG, V51, DOI 10.1117/1.OE.51.9.091603 Hesler J L, 2006, P 7 INT S SPAC TER T, P215 Hintzsche H, 2012, CRIT REV ENV SCI TEC, V42, P2408, DOI 10.1080/10643389.2011.574206 Hishida M, 2011, PHYS REV LETT, V106, DOI 10.1103/PhysRevLett.106.158102 Ho IC, 2010, OPT EXPRESS, V18, P2872, DOI 10.1364/OE.18.002872 HU BB, 1995, OPT LETT, V20, P1716, DOI 10.1364/OL.20.001716 Huang C, 2012, PHYS REV B, V85 Huber R, 2001, NATURE, V414, P286, DOI 10.1038/35104522 Jankowiak A., 2013, Synchrotron Radiation News, V26, P22, DOI 10.1080/08940886.2013.791212 Jepsen PU, 2007, CHEM PHYS LETT, V442, P275, DOI 10.1016/j.cplett.2007.05.112 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Jepsen PU, 2005, OPT LETT, V30, P29, DOI 10.1364/OL.30.000029 JUICE-Jupiter Icy Moons Explorer, 2014, SRE20141 JUICE EUR S, P1 Kallfass I, 2011, IEEE T THZ SCI TECHN, V1, P477, DOI 10.1109/TTHZ.2011.2160021 Kampfrath T, 2013, NAT PHOTONICS, V7, P680, DOI [10.1038/nphoton.2013.184, 10.1038/NPHOTON.2013.184] Kan T, 2015, NAT COMMUN, V6, DOI 10.1038/ncomms9422 Karpowicz N, 2008, APPL PHYS LETT, V92, DOI 10.1063/1.2828709 Kehr SC, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.256403 Kemp MC, 2011, IEEE T THZ SCI TECHN, V1, P282, DOI 10.1109/TTHZ.2011.2159647 Khalid A, 2014, J APPL PHYS, V115, DOI 10.1063/1.4868705 Kirley MP, 2015, IEEE T THZ SCI TECHN, V5, P1012, DOI 10.1109/TTHZ.2015.2468074 Kiwa T, 2003, OPT LETT, V28, P2058, DOI 10.1364/OL.28.002058 Koch M, 2001, NATO SCI SER II MATH, V27, P241 Koenig S, 2013, NAT PHOTONICS, V7, P977, DOI [10.1038/nphoton.2013.275, 10.1038/NPHOTON.2013.275] Kohler R, 2002, NATURE, V417, P156, DOI 10.1038/417156a Koppens FHL, 2014, NAT NANOTECHNOL, V9, P780, DOI [10.1038/nnano.2014.215, 10.1038/NNANO.2014.215] Kosarev A, 2010, SOLID STATE ELECTRON, V54, P417, DOI 10.1016/j.sse.2009.12.032 Kundu I, 2014, OPT EXPRESS, V22, P16595, DOI 10.1364/OE.22.016595 Kuznetsov SA, 2010, KEY ENG MATER, V437, P276, DOI 10.4028/www.scientific.net/KEM.437.276 Langevin Y, 2005, PAYLOAD MISSION DEFI LaRue JL, 2015, PHYS REV LETT, V115, DOI 10.1103/PhysRevLett.115.036103 Leitenstorfer A, 2014, NEW J PHYS, V16, DOI 10.1088/1367-2630/16/4/045016 Leitner DM, 2006, INT REV PHYS CHEM, V25, P553, DOI 10.1080/01442350600862117 Li LH, 2014, ELECTRON LETT, V50, P309, DOI 10.1049/el.2013.4035 Liu L, 2010, IEEE MICROW WIREL CO, V20, P504, DOI 10.1109/LMWC.2010.2055553 Liu SC, 2016, OPT EXPRESS, V24, P2728, DOI 10.1364/OE.24.002728 Lu X H, 2008, P SOC PHOTO-OPT INS, V7277 Luukanen A, 2003, APPL PHYS LETT, V82, P3970, DOI 10.1063/1.1579562 Mann C, 2009, P SOC PHOTO-OPT INS, V7311, P3970 Mickan S, 2004, PROC SPIE, V5277, P54, DOI 10.1117/12.530386 Mineo M, 2010, IEEE T ELECTRON DEV, V57, P3169, DOI 10.1109/TED.2010.2071876 Mittleman DM, 1996, IEEE J SEL TOP QUANT, V2, P679, DOI 10.1109/2944.571768 Mittleman DM, 1999, APPL PHYS B-LASERS O, V68, P1085, DOI 10.1007/s003400050750 Moon K, 2012, APPL PHYS LETT, V101, DOI 10.1063/1.4733475 Muller AS, 2010, REV ACCEL SCI TECH, V3, P165, DOI 10.1142/S1793626810000427 Muller R, 2015, J INFRARED MILLIM TE, V36, P654, DOI 10.1007/s10762-015-0163-7 Naftaly M, 2015, TERAHERTZ METROLOGY, P1 Nagai M, 2015, OPT EXPRESS, V23, P4641, DOI 10.1364/OE.23.004641 Nagatsuma T, 2012, OPT EXPRESS, V21, P477 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Navarro-Cia M, 2015, J INFRARED MILLIM TE, V36, P542, DOI 10.1007/s10762-015-0157-5 Nielsen K, 2009, OPT EXPRESS, V17, P8592, DOI 10.1364/OE.17.008592 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 Nordquist CD, 2011, IEEE J SEL TOP QUANT, V17, P130, DOI 10.1109/JSTQE.2010.2049095 Oh SJ, 2012, J INFRARED MILLIM TE, V33, P74, DOI 10.1007/s10762-011-9847-9 Ojefors E, 2009, IEEE J SOLID-ST CIRC, V44, P1968, DOI 10.1109/JSSC.2009.2021911 Ortolani M, 2008, PHYS REV LETT, V97 Ozerov M, 2014, PHYS REV LETT, V113, DOI 10.1103/PhysRevLett.113.157205 Paoloni C, 2013, IEEE T ELECTRON DEV, V60, P1236, DOI 10.1109/TED.2013.2240686 Parrott EPJ, 2015, APPL SPECTROSC, V69, P1, DOI 10.1366/14-07707 Patrashin M, 2015, IEEE T ELECTRON DEV, V62, P1068, DOI 10.1109/TED.2015.2393358 Peiponen K. E., 2013, TERAHERTZ SPECTROSCO, V171 Peng K, 2015, NANO LETT, V15, P206, DOI 10.1021/nl5033843 Pickwell E, 2004, APPL PHYS LETT, V84, P2190, DOI 10.1063/1.1688448 Ponnampalam L, 2011, J LIGHTWAVE TECHNOL, V29, P2229, DOI 10.1109/JLT.2011.2158186 Pupeza I, 2007, OPT EXPRESS, V15, P4335, DOI 10.1364/OE.15.004335 Rauter P, 2015, LASER PHOTONICS REV, V9, P452, DOI 10.1002/lpor.201500095 Reid CB, 2011, PHYS MED BIOL, V56, P4333, DOI 10.1088/0031-9155/56/14/008 Reid J R, 2012, IEEE 12 TOP M SIL MO, P17 Rosch M, 2015, NAT PHOTONICS, V9, P42, DOI [10.1038/nphoton.2014.279, 10.1038/NPHOTON.2014.279] Rudd JV, 2000, PROC SPIE, V3934, P27, DOI 10.1117/12.386344 Rymanov V, 2015, PHOTONICS, V2, DOI 10.3390/photonics2041152 SANTOS Daisy Conceicao, 2014, THESIS Scherger B, 2011, APPL OPTICS, V50, P2256, DOI 10.1364/AO.50.002256 Schleicher JM, 2009, J APPL PHYS, V105, DOI 10.1063/1.3133093 Schumann S, 2012, OPT EXPRESS, V20, P19200, DOI 10.1364/OE.20.019200 Seeds AJ, 2015, J LIGHTWAVE TECHNOL, V33, P579, DOI 10.1109/JLT.2014.2355137 Sell A, 2008, OPT LETT, V33, P2767, DOI 10.1364/OL.33.002767 Shams H, 2015, IEEE PHOTONICS J, V7, DOI 10.1109/JPHOT.2015.2438437 Shams H, 2014, OPT EXPRESS, V22, P23465, DOI 10.1364/OE.22.023465 Shen YC, 2004, APPL PHYS LETT, V85, P164, DOI 10.1063/1.1768313 Simoens F., 2014, PHILOS T A, V372, P1 Simoens F, 2011, 36 INT C INFR MILL T, P1 Singh A, 2015, OPT EXPRESS, V23, P6656, DOI 10.1364/OE.23.006656 Sirtori C, 2013, NAT PHOTONICS, V7, P691, DOI [10.1038/NPHOTON.2013.208, 10.1038/nphoton.2013.208] SMITH PR, 1988, IEEE J QUANTUM ELECT, V24, P255, DOI 10.1109/3.121 Son JH, 2013, NANOTECHNOLOGY, V24, DOI 10.1088/0957-4484/24/21/214001 Swinyard B, 2013, SPIE SENSORS SYSTEMS Sy S, 2010, PHYS MED BIOL, V55, P7587, DOI 10.1088/0031-9155/55/24/013 Taylor ZD, 2015, IEEE T THZ SCI TECHN, V5, P184, DOI 10.1109/TTHZ.2015.2392628 Teppati V, 2013, CAMB RF MICROW ENG, P1, DOI 10.1017/CBO9781139567626 Tewari P, 2012, P SPIE, V8261 Thomas B., 2014, P 39 INT C INFR MILL, P1 Thumm M, 2014, KIT SCI REPORTS, V7693 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Truong BCQ, 2015, IEEE T BIO-MED ENG, V62, P699, DOI 10.1109/TBME.2014.2364025 Turcinkova D, 2015, APPL PHYS LETT, V106, DOI 10.1063/1.4916653 Turner GM, 2002, J PHYS CHEM B, V106, P11716, DOI 10.1021/jp025844e van der Valk NCJ, 2002, APPL PHYS LETT, V81, P1558, DOI 10.1063/1.1503404 van Dijk F, 2014, IEEE PHOTONIC TECH L, V26, P965, DOI 10.1109/LPT.2014.2309353 Vicario C, 2014, PHYS REV LETT, V112, DOI 10.1103/PhysRevLett.112.213901 Vinh NQ, 2015, J CHEM PHYS, V142, DOI 10.1063/1.4918708 Vitiello MS, 2012, NAT PHOTONICS, V6, P525, DOI 10.1038/nphoton.2012.145 Vitiello MS, 2015, OPT EXPRESS, V23, P5167, DOI 10.1364/OE.23.005167 Vitiello MS, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms6884 Wade A, 2009, NAT PHOTONICS, V3, P41, DOI 10.1038/NPHOTON.2008.251 Wallace B., 2015, SPIE NEWSROOM, DOI [10.1117/2.1201503.005871, DOI 10.1117/2.1201503.005871] Wallace VP, 2004, BRIT J DERMATOL, V151, P424, DOI 10.1111/j.1365-2133.2004.06129.x Wang FH, 2015, OPTICA, V2, P944, DOI 10.1364/OPTICA.2.000944 Weightman P, 2012, PHYS BIOL, V9, DOI 10.1088/1478-3975/9/5/053001 Wienold M, 2014, OPT EXPRESS, V22, P3334, DOI 10.1364/OE.22.003334 Wilk R, 2007, C LAS EL BALT MD Williams BS, 2006, ELECTRON LETT, V42, P89, DOI 10.1049/el:20063921 Williams GP, 2006, REP PROG PHYS, V69, P301, DOI 10.1088/0034-4885/69/2/R01 Williams GP, 2008, NAT PHYS, V4, P356, DOI 10.1038/nphys958 Williams MRC, 2013, J PHYS CHEM B, V117, P10444, DOI 10.1021/jp406730a Williams R, 2013, PHYS MED BIOL, V58, P373, DOI 10.1088/0031-9155/58/2/373 Withayachumnankul W, 2008, J OPT SOC AM B, V25, P1059, DOI 10.1364/JOSAB.25.001059 Woerner M, 2013, NEW J PHYS, V15, DOI 10.1088/1367-2630/15/2/025039 Woodward RM, 2003, J INVEST DERMATOL, V120, P72, DOI 10.1046/j.1523-1747.2003.12013.x Wu X, OPT LETT, V39, P5403 Wu ZR, 2013, REV SCI INSTRUM, V84, DOI 10.1063/1.4790427 Xu J, 2003, PROC SPIE, V5268, P19, DOI 10.1117/12.518533 Yamashita M, 2011, OPT EXPRESS, V19, P10864, DOI 10.1364/OE.19.010864 Yan F, 2013, J INFRARED MILLIM TE, V34, P489, DOI 10.1007/s10762-013-0005-4 Yang SH, 2014, IEEE T THZ SCI TECHN, V4, P575, DOI 10.1109/TTHZ.2014.2342505 Yeh KL, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2734374 Zamora A, 2015, IEEE MTT S INT MICR Zhao JF, 2011, IEEE T ELECTRON DEV, V58, P1221, DOI 10.1109/TED.2011.2109723 Zheludev NI, 2012, NAT MATER, V11, P917, DOI [10.1038/NMAT3431, 10.1038/nmat3431] Zhou Y, 2010, PROG ELECTROMAGN RES, V105, P71, DOI 10.2528/PIER10041806 Zibik EA, 2009, NAT MATER, V8, P803, DOI [10.1038/nmat2511, 10.1038/NMAT2511] Dhillon, S. S. Vitiello, M. S. Linfield, E. H. Davies, A. G. Hoffmann, Matthias C. Booske, John Paoloni, Claudio Gensch, M. Weightman, P. Williams, G. P. Castro-Camus, E. Cumming, D. R. S. Simoens, F. Escorcia-Carranza, I. Grant, J. Lucyszyn, Stepan Kuwata-Gonokami, Makoto Konishi, Kuniaki Koch, Martin Schmuttenmaer, Charles A. Cocker, Tyler L. Huber, Rupert Markelz, A. G. Taylor, Z. D. Wallace, Vincent P. Zeitler, J. Axel Sibik, Juraj Korter, Timothy M. Ellison, B. Rea, S. Goldsmith, P. Cooper, Ken B. Appleby, Roger Pardo, D. Huggard, P. G. Krozer, V. Shams, Haymen Fice, Martyn Renaud, Cyril Seeds, Alwyn Stoehr, Andreas Naftaly, Mira Ridler, Nick Clarke, Roland Cunningham, John E. Johnston, Michael B. Huggard, Peter/U-2150-2019; Konishi, Kuniaki/AAN-3624-2020; Zeitler, J. Axel/B-4885-2008; Paoloni, Claudio/AAH-9824-2019; Hoffmann, Matthias C./N-1082-2019; Wallace, Vincent P/A-9320-2012; Johnston, Michael/B-9813-2008; Castro-Camus, Enrique/V-6861-2019; Krozer, Viktor/P-5623-2014; Hoffmann, Matthias C/B-3893-2009; PAOLONI, CLAUDIO/AAA-3211-2020; Gonokami, Makoto/F-3641-2012; Shams, Haymen/H-3754-2012; Ridler, Nick/AAN-9637-2020; Huber, Rupert/N-4126-2018 Konishi, Kuniaki/0000-0003-2389-9787; Zeitler, J. Axel/0000-0002-4958-0582; Hoffmann, Matthias C./0000-0002-3596-9853; Wallace, Vincent P/0000-0003-3814-5400; Johnston, Michael/0000-0002-0301-8033; Krozer, Viktor/0000-0002-2387-1947; Hoffmann, Matthias C/0000-0002-3596-9853; PAOLONI, CLAUDIO/0000-0002-0265-0862; Shams, Haymen/0000-0002-5333-6478; Huber, Rupert/0000-0001-6617-9283; Davies, Alexander/0000-0002-1987-4846; Seeds, Alwyn/0000-0002-5228-627X; Castro-Camus, Enrique/0000-0002-8218-9155; Cunningham, John/0000-0002-1805-9743; Naftaly, Mira/0000-0002-0671-822X; Cumming, David/0000-0002-7838-8362 Engineering and Physical Sciences Research CouncilUK Research & Innovation (UKRI)Engineering & Physical Sciences Research Council (EPSRC) [EP/P015883/1, EP/M00306X/1, EP/K023349/1, EP/M017095/1, EP/L026597/1, EP/J017671/1] Funding Source: researchfish; Natural Environment Research CouncilUK Research & Innovation (UKRI)NERC Natural Environment Research Council [NER/Z/S/2003/00642, NE/L012375/1, NER/Z/S/2000/01292] Funding Source: researchfish; Science and Technology Facilities CouncilUK Research & Innovation (UKRI)Science & Technology Facilities Council (STFC) [ST/P002056/1] Funding Source: researchfish; Direct For Biological SciencesNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Biological InfrastructureNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Molecular and Cellular BioscienceNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1616529] Funding Source: National Science Foundation 566 30 462 Iop publishing ltd Bristol 1361-6463
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Importance of Protein Vibration Directionality on Function - Niessen, Katherine A.; Xu, Mengyang; Deng, Yanting; Snell, Edward H.; Markelz, Andrea G. (Biophysical Journal, 2017)
Snell, Edward/G-2055-2018 Snell, Edward/0000-0001-8714-3191 1 58th Annual Meeting of the Biophysical-Society Feb 15-19, 2014 San Francisco, CA Biophys Soc

Moving in the right direction: protein vibrations steering function - Niessen, Katherine A; Xu, Mengyang; Paciaroni, Alessandro; Orecchini, Andrea; Snell, Edward H; Markelz, Andrea G (Biophysical Journal, 2017)

Anisotropic Absorption Measurements Reveal Protein Dynamical Transition in Intramolecular Vibrations - Xu, M. Y.; Niessen, K.; Michki, N.; Deng, Y. T.; Snell, E.; Markelz, A. G. (2016 41st International Conference on Infrared, Millimeter, and Terahertz Waves, 2016)
Modeling has predicted that intramolecular structural vibrations enables proteins to access functionally important structural change. We show that the vibrational density of states and the isotropic absorption in the terahertz range are only weakly dependent on the protein functional state for several bench marking proteins. At the same time the direction of motions changes dramatically with functional state and with a resulting impact on the anisotropic absorption. Our anisotropic THz microscopy (ATM) measurements confirm this sensitivity. Here we apply the technique to the question of whether the protein dynamical transition (DT) is important to protein function. We find a strong anisotropic resonance at 70 cm(-1) rapidly increases in strength at temperatures above the DT. As these intramolecular vibrations enable protein structure to change conformation, the results suggest function will cease below DT for those proteins that require large scale conformational change.
ISI Document Delivery No.: BG7KC Times Cited: 0 Cited Reference Count: 4 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Niessen K., 2015, BIOPHYSICAL REV PETHIG R, 1995, PROTEIN SOLVENT INTE, P265 RUPLEY JA, 1991, ADV PROTEIN CHEM, V41, P37 Xu, Mengyang Niessen, Katherine Michki, Nigel Deng, Yanting Snell, Edward Markelz, A. G. Irmmw-thz Proceedings Paper 41st International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Sep 25-30, 2016 Copenhagen, DENMARK DTU, IEEE, QMC Instruments, Danish Ctr Laser Infrastructure, DTU Fotonik, Dept Photon Engn, ARL, Carl Sberg Fdn, AF Off Sci Res, Tech Univ Denmark, IEEE Microwave Theory & Tech Soc, Azpect Photon, Ekspla, Hubner HF Syst Engn, I2S, Laser Quantum, Menlo Syst, Neaspec, Springer, TeraView, Virginia Diodes Snell, Edward/G-2055-2018 Snell, Edward/0000-0001-8714-3191 345 e 47th st, new york, ny 10017 usa 2162-2027

Direct Measurements of the Long-Range Collective Vibrations of Photoactive Yellow Protein - Deng, Yanting; Xu, Mengyang; Niessen, Katherine A.; Schmidt, Marius; Markelz, Andrea G. (30th Anniversary Symposium of The Protein Society, 2016)
Long-range collective vibrations are thought to be crucial to protein functions. In the case of photoactive protein family, modeling suggests the intramolecular vibrations provide an efficient means of energy relaxation[1], feedback for enhancement of chromophore vibrations that promote structural transitions[2] and can assist in charge energy transfer[3]. As a paradigm of this family, photoactive yellow protein (PYP) is a cytoplasmic photocycling protein related to negative phototactic response to blue light in purple photosynthetic bacteria. PYP has a p-coumaric acid chromophore binding to the cysteine residue via a thioester bond, whose vibrations were found to overlap calculated vibrations of the protein scaffold. Using our unique technique of anisotropic terahertz microscopy(ATM)[4], we measure the intramolecular vibrations for PYP for the first time, including cycling between ground and blue shift (pB) states. Room temperature ATM measurements are performed in the dark and with continuous wave illumination at 488nm, resulting in a steady pB state with approximately 5% population conversion. In pB state, we find an overall decrease in the strength of resonant band in frequency range of 30-60 cm-1. Our calculated spectra using quasi-harmonic analysis indicate that our measurements are dominated by the protein vibrations, rather than the pCA chromophore, allowing us to characterize how the scaffold dynamics changes with functional states and mutations. 1. Levantino, M., et al. Nat Commun, 2015. 6. 2. Mataga, N., et al. Chem. Phys. Lett., 2002. 352(3-4): p. 220-225. 3. Fokas, A.S., et al. Photosynth. Res., 2014. 122

Modulated orientation-sensitive terahertz spectroscopy - Singh, R.; George, D. K.; Bae, C. J.; Niessen, K. A.; Markelz, A. G. (Photonics Research, 2016)
Intramolecular vibrations of large macromolecules reside in the terahertz range. In particular, protein vibrations are closely spaced in frequency, resulting in a nearly continuous vibrational density of states. This density of vibrations interferes with the identification of specific absorption lines and their subsequent association with specific functional motions. This challenge is compounded with the absorption being dominated by the solvent and local relaxational motions. A strategy for removing the isotropic relaxational loss and isolating specific vibrations is to use aligned samples and polarization-sensitive measurements. Here, we demonstrate a technique to rapidly attain the anisotropic resonant absorbance using terahertz time domain spectroscopy and a spinning sample. The technique, modulated orientation-sensitive terahertz spectroscopy (MOSTS), has a nonzero signal only for anisotropic samples, as demonstrated by a comparison between a silicon wafer and a wire grid polarizer. For sucrose and oxalic acid molecular crystals, the MOSTS response is in agreement with modeled results for the intermolecular vibrations. Further, we demonstrate that, even in the presence of a large relaxational background, MOSTS isolates underlying vibrational resonances. (C) 2016 Chinese Laser Press
ISI Document Delivery No.: DM9BJ Times Cited: 6 Cited Reference Count: 40 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Aguilar RV, 2012, PHYS REV LETT, V108, DOI 10.1103/PhysRevLett.108.087403 Aschaffenburg DJ, 2012, APPL PHYS LETT, V100, DOI 10.1063/1.4729148 Bahar I, 2005, CURR OPIN STRUC BIOL, V15, P586, DOI 10.1016/j.sbi.2005.08.007 Benkovic SJ, 2003, SCIENCE, V301, P1196, DOI 10.1126/science.1085515 Boehr DD, 2006, CHEM REV, V106, P3055, DOI 10.1021/cr050312q Chen JY, 2005, PHYS REV E, V72, DOI 10.1103/PhysRevE.72.040901 Chen Q, 1999, APPL PHYS LETT, V74, P3435, DOI 10.1063/1.124119 Daniel RM, 2003, ANNU REV BIOPH BIOM, V32, P69, DOI 10.1146/annurev.biophys.32.110601.142445 Diehl M, 1997, BIOPHYS J, V73, P2726, DOI 10.1016/S0006-3495(97)78301-2 Ebbinghaus S, 2007, P NATL ACAD SCI USA, V104, P20749, DOI 10.1073/pnas.0709207104 Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 Fan ST, 2014, J PHYS D APPL PHYS, V47, DOI 10.1088/0022-3727/47/37/374009 Frauenfelder H, 2006, P NATL ACAD SCI USA, V103, P15469, DOI 10.1073/pnas.0607168103 Gabel F, 2002, Q REV BIOPHYS, V35, P327, DOI 10.1017/S0033583502003840 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Giraud G, 2003, BIOPHYS J, V85, P1903, DOI 10.1016/S0006-3495(03)74618-9 Hammes GG, 2011, BIOCHEMISTRY-US, V50, P10422, DOI 10.1021/bi201486f Jackson J.D., 1975, CLASSICAL ELECTRODYN Jenkins GS, 2010, REV SCI INSTRUM, V81, DOI 10.1063/1.3480554 Jepsen PU, 2007, CHEM PHYS LETT, V442, P275, DOI 10.1016/j.cplett.2007.05.112 Karplus M, 2005, P NATL ACAD SCI USA, V102, P6679, DOI 10.1073/pnas.0408930102 Kim SJ, 2008, ANGEW CHEM INT EDIT, V47, P6486, DOI 10.1002/anie.200802281 Kindt JT, 1996, J PHYS CHEM-US, V100, P10373, DOI 10.1021/jp960141g King MD, 2010, J PHYS CHEM A, V114, P7127, DOI 10.1021/jp101935n Kroll J, 2007, VIB SPECTROSC, V43, P324, DOI 10.1016/j.vibspec.2006.03.010 Leitner DM, 2008, HFSP J, V2, P314, DOI 10.2976/1.2976661 Li M, 2011, OPT LETT, V36, P3633, DOI 10.1364/OL.36.003633 Liu D, 2008, PHYS REV LETT, V101, DOI 10.1103/PhysRevLett.101.135501 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 PETHIG R, 1995, PROTEIN SOLVENT INTE, P265 Planken PCM, 2001, J OPT SOC AM B, V18, P313, DOI 10.1364/JOSAB.18.000313 Rheinstadter MC, 2009, PHYS REV LETT, V103, DOI 10.1103/PhysRevLett.103.128104 RUPLEY JA, 1991, ADV PROTEIN CHEM, V41, P37 Singh R, 2012, J PHYS CHEM A, V116, P10359, DOI 10.1021/jp307288r TORGESEN JL, 1964, SCIENCE, V146, P53, DOI 10.1126/science.146.3640.53 Vinh NQ, 2011, J AM CHEM SOC, V133, P8942, DOI 10.1021/ja200566u Walther M, 2003, CHEM PHYS, V288, P261, DOI 10.1016/S0301-0104(03)00031-4 Xu J, 2006, J PHYS CHEM B, V110, P24255, DOI 10.1021/jp064830w Yasumatsu N, 2012, REV SCI INSTRUM, V83, DOI 10.1063/1.3683570 Singh, Rohit George, Deepu Koshy Bae, Chejin Niessen, K. A. Markelz, A. G. George, Deepu/J-9882-2014 George, Deepu/0000-0003-0021-0705 National Science Foundation (NSF)National Science Foundation (NSF) [DBI2959989]; University at Buffalo (UB) [1126960-1-68255]; Los Alamos National Laboratory (LANL)United States Department of Energy (DOE)Los Alamos National Laboratory [1125895-1-71842]; Direct For Biological SciencesNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Biological InfrastructureNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation National Science Foundation (NSF) (DBI2959989); University at Buffalo (UB) (Holm Fund 1126960-1-68255); Los Alamos National Laboratory (LANL) (Molecular Crystal Studies 1125895-1-71842). 6 26 Optical soc amer Washington
Keywords: absorption-spectroscopy; dynamics; enzyme catalysis; low-frequency modes; lysozyme; neutron-scattering; Optics; perspective; polarization modulation; proteins; water

The Role of Dynamical Transition in Protein Function: Coupling of Protein Collective Vibrations and Water Dynamics - Xu, Mengyang; Niessen, Katherine; Deng, Yanting; Michki, Nigel; Snell, Edward; Markelz, Andrea (30th Anniversary Symposium of The Protein Society, 2016)
Computational simulations have revealed protein collective vibrations prompt structural rearrangements to accomplish biological function. However, the biological importance of collective vibrations has not been experimentally demonstrated. The attempts have been hampered by the inability to distinguish localized water or side-chain relaxational motions from protein long-range vibrations using conventional techniques. The dynamical transition (DT), extensively observed using X-ray, neutron scattering, NMR and terahertz techniques [1,2], describes a rapid increase in the temperature-dependent dynamics of critically hydrated proteins above ∼220 K, and has been attributed to thermally activated solvent motions. While some proteins lose function below the specific temperature, others do not. We suggest the difference arises from the nature of the required motions for function. Specifically, functional motions enabled by long-range vibrations will be vulnerable to DT, which require surrounding solvent to be sufficiently mobile. We explored the coupling of protein vibrations to solvent dynamics by applying a recently developed technique, anisotropy terahertz microscopy [3], to directly measure the collective vibrations for lysozyme and investigate the temperature dependence in 150-300 K range. We find long-range intramolecular vibrations occur at 220K and rapidly increase in strength with increasing temperature, consistent with enhanced access above the DT. The results suggest collective vibrations are slaved to DT, and those proteins with function reliant on these motions will cease function below DT. 1. Doster,W., et al. Phys.Rev.Lett., 2010.104(9):098101. 2. Niessen,K., et al. Biophys.Rev., 2015.7,201. 3. Acbas,G., et al. Nat.Commun., 2014.5,3076.

Measurements and Calculations of Protein Intramolecular Vibrations in the THz Range - Niessen, K. A.; Snell, E.; Markelz, A. G. (2014 39th International Conference on Infrared, Millimeter, and Terahertz Waves, 2014)
We report the calculations and measurements of intramolecular vibrational modes and their dependence on inhibitor binding in the THz range. We see an increase in anisotropic THz absorption at low frequency with inhibitor binding in both the measurements and calculations. This surprising result suggests an increase in flexibility with binding. We will discuss the possible reasons for this discrepancy.
ISI Document Delivery No.: BF0IL Times Cited: 0 Cited Reference Count: 13 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Balog E, 2004, PHYS REV LETT, V93, DOI 10.1103/PhysRevLett.93.028103 Best RB, 2012, J CHEM THEORY COMPUT, V8, P3257, DOI 10.1021/ct300400x BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 BRUCCOLERI RE, 1986, BIOPOLYMERS, V25, P1767, DOI 10.1002/bip.360250916 CHEETHAM JC, 1992, J MOL BIOL, V224, P613, DOI 10.1016/0022-2836(92)90548-X Dong J, 1999, ACTA CRYSTALLOGR D, V55, P745, DOI 10.1107/S0907444998016047 Guo JN, 2014, BIOCHEMISTRY-US, V53, P2855, DOI 10.1021/bi500238q Hammes-Schiffer S, 2006, ANNU REV BIOCHEM, V75, P519, DOI 10.1146/annurev.biochem.75.103004.142800 Henzler-Wildman KA, 2007, NATURE, V450, P838, DOI 10.1038/nature06410 Jo S, 2008, J COMPUT CHEM, V29, P1859, DOI 10.1002/jcc.20945 PERUTZ MF, 1970, NATURE, V228, P726, DOI 10.1038/228726a0 TEETER MM, 1990, J PHYS CHEM-US, V94, P8091, DOI 10.1021/j100384a021 Niessen, Katherine A. Snell, Edward Markelz, A. G. Irmmw-thz Proceedings Paper 39th International Conference on Infrared, Millimeter, and Terahertz waves (IRMMW-THz) Sep 14-19, 2014 Tucson, AZ THORLABS, Tydex, TOPTICA Photon, Bruker, Gentec EO, Lake Shore Cryotron, Ekspla, Zomega, TeraSense, Insight Product, Emcore, QMC Instruments, TeraView, NeaSpec, Advantest, MenloSystems, Traycer, Microtech Instruments Inc, LongWave Photon, Virginia Diodes Inc, ASU, MTT S, Journal Infrared Millimeter & Tera Hertz Waves, Tera Hertz Sci & Technol, Army Res Off Snell, Edward/G-2055-2018 Snell, Edward/0000-0001-8714-3191 345 e 47th st, new york, ny 10017 usa 2162-2027
Keywords: charmm

Optical measurements of long-range protein vibrations - Acbas, G.; Niessen, K. A.; Snell, E. H.; Markelz, A. G. (Nature Communications, 2014)
Protein biological function depends on structural flexibility and change. From cellular communication through membrane ion channels to oxygen uptake and delivery by haemoglobin, structural changes are critical. It has been suggested that vibrations that extend through the protein play a crucial role in controlling these structural changes. While nature may utilize such long-range vibrations for optimization of biological processes, bench-top characterization of these extended structural motions for engineered biochemistry has been elusive. Here we show the first optical observation of long-range protein vibrational modes. This is achieved by orientation-sensitive terahertz near-field microscopy measurements of chicken egg white lysozyme single crystals. Underdamped modes are found to exist for frequencies >10 cm(-1). The existence of these persisting motions indicates that damping and intermode coupling are weaker than previously assumed. The methodology developed permits protein engineering based on dynamical network optimization.
ISI Document Delivery No.: AA4RQ Times Cited: 101 Cited Reference Count: 48 Cited References: AUSTIN RH, 1989, PHYS REV LETT, V62, P1912, DOI 10.1103/PhysRevLett.62.1912 Bahar I, 2005, CURR OPIN STRUC BIOL, V15, P586, DOI 10.1016/j.sbi.2005.08.007 Balabin IA, 2000, SCIENCE, V290, P114, DOI 10.1126/science.290.5489.114 Balog E, 2004, PHYS REV LETT, V93, DOI 10.1103/PhysRevLett.93.028103 Barth A, 2002, Q REV BIOPHYS, V35, P369, DOI 10.1017/S0033583502003815 Benkovic SJ, 2003, SCIENCE, V301, P1196, DOI 10.1126/science.1085515 Brooks BR, 2009, J COMPUT CHEM, V30, P1545, DOI 10.1002/jcc.21287 BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 Brooks CL, 1988, PROTEINS THEORETICAL Chen JY, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2748852 Chen JY, 2005, PHYS REV E, V72, DOI 10.1103/PhysRevE.72.040901 Ding T, 2012, VIB SPECTROSC, V61, P144, DOI 10.1016/j.vibspec.2012.02.020 GENZEL L, 1976, BIOPOLYMERS, V15, P219, DOI 10.1002/bip.1976.360150115 George DK, 2013, IEEE T THZ SCI TECHN, V3, P288, DOI 10.1109/TTHZ.2013.2256233 GRISCHKOWSKY D, 1990, J OPT SOC AM B, V7, P2006, DOI 10.1364/JOSAB.7.002006 Hafner J, 2011, J CHEM PHYS, V135, DOI 10.1063/1.3646312 Hammes GG, 2002, BIOCHEMISTRY-US, V41, P8221, DOI 10.1021/bi0260839 He YF, 2011, BIOPHYS J, V100, P1058, DOI 10.1016/j.bpj.2010.12.3731 KACHALOVA GS, 1991, FEBS LETT, V284, P91, DOI 10.1016/0014-5793(91)80769-Y Karplus M, 2005, P NATL ACAD SCI USA, V102, P6679, DOI 10.1073/pnas.0408930102 Knab J, 2006, BIOPHYS J, V90, P2576, DOI 10.1529/biophysj.105.069088 Knab JR, 2010, APPL PHYS LETT, V97, DOI 10.1063/1.3467192 LEVY RM, 1984, J PHYS CHEM-US, V88, P4233, DOI 10.1021/j150663a009 Lipps F, 2012, PHYS CHEM CHEM PHYS, V14, P6375, DOI 10.1039/c2cp23760a Liu D, 2008, PHYS REV LETT, V101, DOI 10.1103/PhysRevLett.101.135501 MacKerell AD, 1998, J PHYS CHEM B, V102, P3586, DOI 10.1021/jp973084f Markelz AG, 2008, IEEE J SEL TOP QUANT, V14, P180, DOI 10.1109/JSTQE.2007.913424 Meinhold L, 2007, PHYS REV LETT, V99, DOI 10.1103/PhysRevLett.99.138101 Meinhold L, 2007, PROTEINS, V66, P941, DOI 10.1002/prot.21246 Mittleman D.M., 2003, SENSING TERAHERTZ RA MOELLER KD, 1992, BIOPHYS J, V61, P276, DOI 10.1016/S0006-3495(92)81834-9 Perutz MF, 1998, ANNU REV BIOPH BIOM, V27, P1, DOI 10.1146/annurev.biophys.27.1.1 Planken PCM, 2011, J INFRARED MILLIM TE, V32, P975, DOI 10.1007/s10762-011-9824-3 Rheinstadter MC, 2009, PHYS REV LETT, V103, DOI 10.1103/PhysRevLett.103.128104 Sakai K., 2005, TERAHERTZ OPTOELECTR Schumacher M, 2002, NATURE, V417, P501, DOI 10.1038/417501a Siegrist K, 2006, J AM CHEM SOC, V128, P5764, DOI 10.1021/ja058176u Singh R, 2012, J PHYS CHEM A, V116, P10359, DOI 10.1021/jp307288r SMITH J, 1990, J CHEM PHYS, V93, P2974, DOI 10.1063/1.458885 SMITH JC, 1991, Q REV BIOPHYS, V24, P227, DOI 10.1017/S0033583500003723 TEETER MM, 1990, J PHYS CHEM-US, V94, P8091, DOI 10.1021/j100384a021 TIDOR B, 1994, J MOL BIOL, V238, P405, DOI 10.1006/jmbi.1994.1300 Tych KM, 2011, J APPL CRYSTALLOGR, V44, P129, DOI 10.1107/S0021889810043372 Urabe H, 1998, BIOPHYS J, V74, P1533, DOI 10.1016/S0006-3495(98)77865-8 Walther M, 2003, CHEM PHYS, V288, P261, DOI 10.1016/S0301-0104(03)00031-4 WU Q, 1995, APPL PHYS LETT, V67, P3523, DOI 10.1063/1.114909 Xie AH, 2002, PHYS REV LETT, V88, DOI 10.1103/PhysRevLett.88.018102 Xu J, 2006, J PHYS CHEM B, V110, P24255, DOI 10.1021/jp064830w Acbas, Gheorghe Niessen, Katherine A. Snell, Edward H. Markelz, A. G. Snell, Edward/G-2055-2018 Snell, Edward/0000-0001-8714-3191; Markelz, Andrea/0000-0003-0443-4319 National Science Foundation MRIboolean AND2 grant [DBI2959989] We thank Yunfen He and Benjamin Keen for their assistance with calculations. All calculations performed using facilities provided by The Center for Computational Research, SUNY, Buffalo. We thank the National Science Foundation MRI boolean AND 2 grant DBI2959989 for support. 101 4 108 Nature publishing group London
Keywords: absorption; crystals; dynamics; frequency raman-spectra; hydration; lysozyme; motions; Science & Technology - Other Topics; sensitivity; simulations; spectroscopy

Measuring phonons in protein crystals - Acbas, G.; Niessen, K. A.; George, D. K.; Snell, E.; Markelz, A. G. (Ultrafast Phenomena and Nanophotonics Xvii, 2013)
Using Terahertz near field microscopy we find orientation dependent narrow band absorption features for lysozyme crystals. Here we discuss identification of protein collective modes associated with the observed features. Using normal mode calculations we find good agreement with several of the measured features, suggesting that the modes arise from internal molecular motions and not crystal phonons. Such internal modes have been associated with protein function.
ISI Document Delivery No.: BGG42 Times Cited: 0 Cited Reference Count: 5 Cited References: Bahar I, 2005, CURR OPIN STRUC BIOL, V15, P586, DOI 10.1016/j.sbi.2005.08.007 BROOKS B, 1985, P NATL ACAD SCI USA, V82, P4995, DOI 10.1073/pnas.82.15.4995 BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 Karplus M, 2005, P NATL ACAD SCI USA, V102, P6679, DOI 10.1073/pnas.0408930102 Planken PCM, 2011, J INFRARED MILLIM TE, V32, P975, DOI 10.1007/s10762-011-9824-3 Acbas, Gheorghe Niessen, Katherine A. George, Deepu K. Snell, Edward Markelz, A. G. Proceedings Paper Conference on Ultrafast Phenomena and Nanophotonics XVII Feb 03-06, 2013 San Francisco, CA SPIE, Femtolasers Inc Snell, Edward/G-2055-2018; George, Deepu/J-9882-2014 Snell, Edward/0000-0001-8714-3191; George, Deepu/0000-0003-0021-0705; Markelz, Andrea/0000-0003-0443-4319 National Science Foundation MRI2 [DBI2959989] We thank the National Science Foundation MRI2 grant DBI2959989 for support. 1000 20th st, po box 10, bellingham, wa 98227-0010 usa 0277-786x 862305
Keywords: correlated motions; dynamics; mode; molecular crystals; molecular vibrations; normal modes; phonons; protein dynamics; spectroscopy; Terahertz

Improved mode assignment for molecular crystals through anisotropic terahertz spectroscopy - Singh, Rohit; George, Deepu Koshy; Benedict, Jason B; Korter, Timothy M; Markelz, Andrea G (The Journal of Physical Chemistry A, 2012)

Multi-component response in multilayer graphene revealed through terahertz and infrared magneto-spectroscopy - Ellis, C. T.; Stier, A. V.; George, D. K.; Tischler, J. G.; Glaser, E. R.; Myers-Ward, R. L.; Tedesco, J. L.; Eddy, C. R.; Gaskill, D. K.; Markelz, A. G.; Cerne, J. (37th International Conference on Infrared, Millimeter, and Terahertz Waves, 2012)

Orientation Sensitive Terahertz Resonances Observed in Protein Crystals - Acbas, G.; Snell, E.; Markelz, A. G. (2012 37th International Conference on Infrared, Millimeter, and Terahertz Waves, 2012)
A method is presented for measuring anisotropic THz response for small crystals, Crystal Anisotropy Terahertz Microscopy (CATM). Sucrose CATM measurements find the expected anisotropic phonon resonances. CATM measurements of protein crystals find the expected broadband water absorption is suppressed and strong orientation and hydration dependent resonant features.
ISI Document Delivery No.: BJT74 Times Cited: 1 Cited Reference Count: 15 Cited References: Arora K, 2007, P NATL ACAD SCI USA, V104, P18496, DOI 10.1073/pnas.0706443104 Bahar I, 2005, CURR OPIN STRUC BIOL, V15, P586, DOI 10.1016/j.sbi.2005.08.007 Balu R, 2008, BIOPHYS J, V94, P3217, DOI 10.1529/biophysj.107.105163 BROOKS B, 1985, P NATL ACAD SCI USA, V82, P4995, DOI 10.1073/pnas.82.15.4995 Goodey NM, 2008, NAT CHEM BIOL, V4, P474, DOI 10.1038/nchembio.98 Hammes-Schiffer S, 2006, ANNU REV BIOCHEM, V75, P519, DOI 10.1146/annurev.biochem.75.103004.142800 Jarymowycz VA, 2006, CHEM REV, V106, P1624, DOI 10.1021/cr040421p Karplus M, 2005, P NATL ACAD SCI USA, V102, P6679, DOI 10.1073/pnas.0408930102 Knab JR, 2010, APPL PHYS LETT, V97, DOI 10.1063/1.3467192 Lange OF, 2008, SCIENCE, V320, P1471, DOI 10.1126/science.1157092 Liu D, 2008, PHYS REV LETT, V101, DOI 10.1103/PhysRevLett.101.135501 Mellinger JS, 2007, J PHYS CHEM A, V111, P10977, DOI 10.1021/jp074975i Planken PCM, 2011, J INFRARED MILLIM TE, V32, P975, DOI 10.1007/s10762-011-9824-3 Rheinstadter MC, 2009, PHYS REV LETT, V103, DOI 10.1103/PhysRevLett.103.128104 Tych KM, 2011, J APPL CRYSTALLOGR, V44, P129, DOI 10.1107/S0021889810043372 Acbas, Gheorghe Snell, Edward Markelz, A. G. Irmmw-thz Proceedings Paper 37th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Sep 23-28, 2012 Univ Wollongong, Wollongong, AUSTRALIA IEEE, USN, Off Naval Res Sci & Technol, ETRI, UOW, Sch Engn Phys, Ctr Ultrahigh Bandwidth Devices Opt Syst, Victoria Suntech Adv Solar Facil, Swinburne, Ctr Micro Photon, Edinburgh Photon, Tydex, TRAS Inc, Inst Photon & Opt Sci, LakeShore, Australian Synchrotron, CSIRO, Univ Wollongong, Inst Superconducting & Elect Mat, Ctr Med Radiat Phys, Univ Sydney, IEEE Microwave Theory & Tech Soc Snell, Edward/G-2055-2018 Snell, Edward/0000-0001-8714-3191 345 e 47th st, new york, ny 10017 usa 2162-2027
Keywords: dynamics; mode

Terahertz magneto-optical polarization modulation spectroscopy - George, Deepu K; Stier, Andreas V; Ellis, Chase T; McCombe, Bruce D; Černe, John; Markelz, Andrea G (JOSA BJOSA B, 2012)

Terahertz Response and Colossal Kerr Rotation from the Surface States of the Topological Insulator Bi2Se3 - Aguilar, R. V.; Stier, A. V.; Liu, W.; Bilbro, L. S.; George, D. K.; Bansal, N.; Wu, L.; Cerne, J.; Markelz, A. G.; Oh, S.; Armitage, N. P. (Physical Review Letters, 2012)
We report the THz response of thin films of the topological insulator Bi2Se3. At low frequencies, transport is essentially thickness independent showing the dominant contribution of the surface electrons. Despite their extended exposure to ambient conditions, these surfaces exhibit robust properties including narrow, almost thickness-independent Drude peaks, and an unprecedentedly large polarization rotation of linearly polarized light reflected in an applied magnetic field. This Kerr rotation can be as large as 65 degrees and can be explained by a cyclotron resonance effect of the surface states.
ISI Document Delivery No.: 896NY Times Cited: 164 Cited Reference Count: 35 Cited References: Akhmerov AR, 2009, PHYS REV LETT, V102, DOI 10.1103/PhysRevLett.102.216404 Alpichshev Z, 2010, PHYS REV LETT, V104, DOI 10.1103/PhysRevLett.104.016401 Analytis JG, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.205407 Bansal N., ARXIV11045709 Benia HM, 2011, PHYS REV LETT, V107, DOI 10.1103/PhysRevLett.107.177602 Bianchi M, 2010, NAT COMMUN, V1, DOI 10.1038/ncomms1131 Butch NP, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.241301 Chen J, 2011, PHYS REV B, V83, DOI 10.1103/PhysRevB.83.241304 Chen YL, 2009, SCIENCE, V325, P178, DOI 10.1126/science.1173034 Essin AM, 2009, PHYS REV LETT, V102, DOI 10.1103/PhysRevLett.102.146805 Eto K, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.195309 Fu L, 2007, PHYS REV B, V76, DOI 10.1103/PhysRevB.76.045302 Fu L, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.096407 Hsieh D, 2008, NATURE, V452, P970, DOI 10.1038/nature06843 Hsieh D, 2009, NATURE, V460, P1101, DOI 10.1038/nature08234 Jenkins GS, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.125120 King PDC, 2011, PHYS REV LETT, V107, DOI 10.1103/PhysRevLett.107.096802 LaForge AD, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.125120 Lan YP, 2011, PHYS REV B, V83, DOI 10.1103/PhysRevB.83.205109 Maciejko J, 2010, PHYS REV LETT, V105, DOI 10.1103/PhysRevLett.105.166803 Moore JE, 2007, PHYS REV B, V75, DOI 10.1103/PhysRevB.75.121306 Qi XL, 2008, PHYS REV B, V78, DOI 10.1103/PhysRevB.78.195424 Qu DX, 2010, SCIENCE, V329, P821, DOI 10.1126/science.1189792 Roushan P, 2009, NATURE, V460, P1106, DOI 10.1038/nature08308 Roy R, 2009, PHYS REV B, V79, DOI 10.1103/PhysRevB.79.195322 Steinberg H, 2011, PHYS REV B, V84, DOI 10.1103/PhysRevB.84.233101 Sushkov AB, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.125110 THOULESS DJ, 1982, PHYS REV LETT, V49, P405, DOI 10.1103/PhysRevLett.49.405 Tkachov G, 2011, PHYS REV B, V84, DOI 10.1103/PhysRevB.84.035405 Tse WK, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.161104 Tse WK, 2010, PHYS REV LETT, V105, DOI 10.1103/PhysRevLett.105.057401 VONKLITZING K, 1980, PHYS REV LETT, V45, P494, DOI 10.1103/physrevlett.45.494 Xia Y, 2009, NAT PHYS, V5, P398, DOI 10.1038/NPHYS1274 Xiong J., PHYSICA A E IN PRESS Zhang XA, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.245107 Aguilar, R. Valdes Stier, A. V. Liu, W. Bilbro, L. S. George, D. K. Bansal, N. Wu, L. Cerne, J. Markelz, A. G. Oh, S. Armitage, N. P. George, Deepu/J-9882-2014; Aguilar, Rolando Valdes/A-6637-2012; Liu, Wei/H-5999-2012; Wu, Liang/C-8715-2015 George, Deepu/0000-0003-0021-0705; Aguilar, Rolando Valdes/0000-0002-4321-4792; Wu, Liang/0000-0003-1696-7809; Markelz, Andrea/0000-0003-0443-4319 "Institute for Quantum Matter" DOE [DE-FG02-08ER46544]; Gordon and Betty Moore FoundationGordon and Betty Moore Foundation; NSFNational Science Foundation (NSF) [MRI-R2 0959989, DMR-1006078, DMR-0845464]; IAMDN of Rutgers University; ONROffice of Naval Research [N000140910749]; Division Of Materials ResearchNational Science Foundation (NSF)NSF - Directorate for Mathematical & Physical Sciences (MPS) [0845464] Funding Source: National Science Foundation The authors would like to thank H. D. Drew, J. Hancock, Z. Hao, G. S. Jenkins, A. Kuzmenko, A. MacDonald, N. A. Mecholsky, A. J. Pearson, O. Tchernyshyov, W-K. Tse, and Y. Wan for helpful discussions and/or correspondences. Support for the measurements at JHU was provided under the auspices of the "Institute for Quantum Matter" DOE DE-FG02-08ER46544 and the Gordon and Betty Moore Foundation. The work at UB was supported by NSF MRI-R2 0959989 and NSF DMR-1006078. The work at Rutgers was supported by IAMDN of Rutgers University, NSF DMR-0845464 and ONR N000140910749. 166 3 157 Amer physical soc College pk
Keywords: bi2te3; Physics

Magneto Optical Polarization Measurements using THz Polarization Modulation Spectroscopy - Stier, A. V.; George, D.; Markelz, A. G.; Cerne, J. (2011 36th International Conference on Infrared, Millimeter, and Terahertz Waves, 2011)
We report a new broad band technique for rapidly measuring the complex Faraday and Kerr rotations in materials such as topological insulators and graphene, combining the distinct advantages of THz time domain spectroscopy and polarization modulation techniques. The performance of the system is demonstrated using GaAs two dimensional electron gas in a magnetic field.
ISI Document Delivery No.: BJT73 Times Cited: 0 Cited Reference Count: 3 Cited References: Cerne J, 2000, PHYS REV B, V61, P8133, DOI 10.1103/PhysRevB.61.8133 Crassee I, 2011, NAT PHYS, V7, P48, DOI 10.1038/NPHYS1816 Tse WK, 2010, PHYS REV LETT, V105, DOI 10.1103/PhysRevLett.105.057401 Stier, A. V. George, D. Markelz, A. G. Cerne, J. Irmmw-thz Proceedings Paper 36th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Oct 02-07, 2011 Houston, TX Rice Univ, IEEE Microwave Theory & Tech Soc, NASA, California Inst Technol, Jet Prop Lab, Univ Wollongong George, Deepu/J-9882-2014 George, Deepu/0000-0003-0021-0705 345 e 47th st, new york, ny 10017 usa 2162-2027

Characterization of Phonons in Molecular Crystals - Singh, R.; George, D.; Markelz, A. G. (Frontiers in Optics 2010, 2010)
We demonstrate a new technique for characterizing the phonons in molecular crystals, Modulated Orientation Sensitive Terahertz Spectroscopy (MOSTS). The technique suppresses crystal defects and solvent contributions, and enhances contributions due to molecular structure and anisotropy.

Terahertz response of quantum point contacts - Song, J. W.; Kabir, N. A.; Kawano, Y.; Ishibashi, K.; Aizin, G. R.; Mourokh, L.; Reno, J. L.; Markelz, A. G.; Bird, J. P. (Applied Physics LettersApplied Physics LettersApplied Physics Letters, 2008)
We measure a clear terahertz response in the low-temperature conductance of a quantum point contact at 1.4 and 2.5 THz. We show that this photoresponse does not arise from a heating effect, but that it is instead excellently described by a classical model of terahertz-induced gate-voltage rectification. This effect is distinct from the rectification mechanisms that have been studied previously, being determined by the phase-dependent interference of the source drain and gate voltage modulations induced by the terahertz field. (C) 2008 American Institute of Physics.
ISI Document Delivery No.: 310KL Times Cited: 25 Cited Reference Count: 21 Cited References: Aizin GR, 2007, APPL PHYS LETT, V91, DOI 10.1063/1.2800369 ARNONE DD, 1995, APPL PHYS LETT, V66, P3149, DOI 10.1063/1.113705 FENG SC, 1993, PHYS REV B, V48, P5354, DOI 10.1103/PhysRevB.48.5354 Hashiba H, 2004, APPL PHYS LETT, V85, P6036, DOI 10.1063/1.1834716 HU Q, 1993, APPL PHYS LETT, V62, P837, DOI 10.1063/1.108567 Hu Q, 1996, SEMICOND SCI TECH, V11, P1888, DOI 10.1088/0268-1242/11/12/021 JANSSEN TJBM, 1994, J PHYS-CONDENS MAT, V6, pL163, DOI 10.1088/0953-8984/6/13/002 Kabir NA, 2006, APPL PHYS LETT, V89, DOI 10.1063/1.2357605 KARADI C, 1994, J OPT SOC AM B, V11, P2566, DOI 10.1364/JOSAB.11.002566 Knap W, 2002, APPL PHYS LETT, V81, P4637, DOI 10.1063/1.1525851 Knap W, 2002, APPL PHYS LETT, V80, P3433, DOI 10.1063/1.1473685 Lee M, 2005, APPL PHYS LETT, V86, DOI 10.1063/1.1851606 MITTLEMAN D, 2002, SPRINGER SERIES OPTI Peralta XG, 2002, APPL PHYS LETT, V81, P1627, DOI 10.1063/1.1497433 Ryzhii V, 2006, JPN J APPL PHYS 2, V45, pL1118, DOI 10.1143/JJAP.45.L1118 Shaner EA, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2735943 Shaner EA, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2128057 Teppe F, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2005394 VANHOUTEN H, 1992, SEMICONDUCT SEMIMET, P9 WYSS RA, 1993, APPL PHYS LETT, V63, P1522, DOI 10.1063/1.110736 WYSS RA, 1995, APPL PHYS LETT, V66, P1144, DOI 10.1063/1.113840 Song, J. W. Kabir, N. A. Kawano, Y. Ishibashi, K. Aizin, G. R. Mourokh, L. Reno, J. L. Markelz, A. G. Bird, J. P. Ishibashi, Koji/G-7065-2012; Bird, Jonathan P/G-4068-2010 Ishibashi, Koji/0000-0001-8131-9969; Bird, Jonathan P/0000-0002-6966-9007; Markelz, Andrea/0000-0003-0443-4319 27 6 Amer inst physics Melville 1077-3118
Keywords: detector; devices; field-effect transistors; Physics; plasma-waves; radiation; resonant detection; subterahertz; transport

Terahertz transmission characteristics of high-mobility GaAs and InAs two-dimensional-electron-gas systems - Kabir, N. A.; Yoon, Y.; Knab, J. R.; Chen, J. Y.; Markelz, A. G.; Reno, J. L.; Sadofyev, Y.; Johnson, S.; Zhang, Y. H.; Bird, J. P. (Applied Physics Letters, 2006)
Frequency-dependent complex conductivity of high-mobility GaAs and InAs two-dimensional-electron-gas (2DEG) systems is studied by terahertz time domain spectroscopy. Determining the momentum relaxation time from a Drude model, the authors find a lower value than that from dc measurements, particularly at high frequencies/low temperatures. These deviations are consistent with the ratio tau(t)/tau(q,) where tau(q) is the full scattering time. This suggests that small-angle scattering leads to weaker heating of 2DEGs at low temperatures than expected from dc mobilit9y. (c) 2006 American Institute of Physics.
ISI Document Delivery No.: 089JE Times Cited: 18 Cited Reference Count: 16 Cited References: ANDO T, 1982, REV MOD PHYS, V54, P437, DOI 10.1103/RevModPhys.54.437 ANDO T, 1989, HIGH MAGNETIC FIELDS, V2, P164 Ashcroft NW, 1976, SOLID STATE PHYS, P1 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Cerne J, 2000, PHYS REV B, V61, P8133, DOI 10.1103/PhysRevB.61.8133 COLERIDGE PT, 1991, PHYS REV B, V44, P3793, DOI 10.1103/PhysRevB.44.3793 Dorozhkin PS, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2035883 Knap W, 2002, APPL PHYS LETT, V81, P4637, DOI 10.1063/1.1525851 Knap W, 2002, APPL PHYS LETT, V80, P3433, DOI 10.1063/1.1473685 Kukushkin IV, 2005, APPL PHYS LETT, V86, DOI 10.1063/1.1856143 MADELUNG O, 1996, SEMICONDUCTORS BASIC, P109 MCKNIGHT SW, 1987, INFRARED PHYS, V27, P327, DOI 10.1016/0020-0891(87)90074-1 Peralta XG, 2002, APPL PHYS LETT, V81, P1627, DOI 10.1063/1.1497433 Sadofyev YG, 2002, APPL PHYS LETT, V81, P1833, DOI 10.1063/1.1504882 Shaner EA, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2128057 ZAWADZKI W, 1974, ADV PHYS, V23, P435, DOI 10.1080/00018737400101371 Kabir, N. A. Yoon, Y. Knab, J. R. Chen, J. -Y. Markelz, A. G. Reno, J. L. Sadofyev, Y. Johnson, S. Zhang, Y. -H. Bird, J. P. Bird, Jonathan P/G-4068-2010 Bird, Jonathan P/0000-0002-6966-9007; Markelz, Andrea/0000-0003-0443-4319 18 15 Amer inst physics Melville
Keywords: field-effect transistors; photoconductivity; Physics; plasma-waves; radiation; resonant detection; subterahertz

Critical hydration and temperature effects on terahertz biomolecular sensing - Knab, Joseph; Shah, Binni; Chen, Jing-Yin; Markelz, Andrea (Chemical and Biological Standoff Detection III, 2005)

Direct measurements of optical phonons in SrTiO3 nanosystems - Wolpert, D; Korolev, K; Sachs, S; Knab, J; Cox, W; Cerne, J; Markelz, A.G; Zhao, T; Ramesh, R; Moeckly, B.H (Physica E: Low-dimensional Systems and Nanostructures, 2003)
We use terahertz time domain spectroscopy to examine finite size effects on the optical phonon modes in SrTiO3 thin films. In temperature-dependent measurements we find a near absence of mode softening in the TO1 phonon frequency. Furthermore we see an increase in the soft mode frequency with reduced thickness. Both of these results correlate well with the reduced dielectric response observed for nanoscale ferroelectric systems.
Keywords: Ferroelectrics; Finite size; Mode softening; phonons; Strontium titanate; Terahertz

Temperature of quasi-two-dimensional electron gases under steady-state terahertz drive - Asmar, N. G.; Cerne, J.; Markelz, A. G.; Gwinn, E. G.; Sherwin, M. S.; Campman, K. L.; Gossard, A. C. (Applied Physics Letters, 1996)
We use photoluminescence to study the time-average energy distribution of electrons in the presence of strong steady-state drive at terahertz (THz) frequencies, in a modulation-doped 125 Angstrom AlGaAs/GaAs square well that is held at low lattice temperature TL. We find that the energy distribution can be characterized by an effective electron temperature, T-e(>T-L), that agrees well with values estimated from the THz-illuminated, dc conductivity. This agreement indicates that under strong THz drive, LO phonon scattering dominates both energy and momentum relaxation; that the carrier distribution maintains a heated, thermal form; and that phonon drift effects are negligible. (C) 1996 American Institute of Physics.
ISI Document Delivery No.: TT663 Times Cited: 59 Cited Reference Count: 12 Cited References: ASMAR NG, 1995, PHYS REV B, V51, P18041, DOI 10.1103/PhysRevB.51.18041 BETHUNE DS, 1989, J OPT SOC AM B, V6, P910, DOI 10.1364/JOSAB.6.000910 CERNE J, 1995, PHYS REV B, V51, P5253, DOI 10.1103/PhysRevB.51.5253 CONWELL E, 1967, SOLID STATE PHYS S, V9 GUPTA R, 1992, PHYS REV B, V46, P7745, DOI 10.1103/PhysRevB.46.7745 HEYMAN JN, 1994, PHYS REV LETT, V72, P2183, DOI 10.1103/PhysRevLett.72.2183 KOMIYAMA S, 1985, PHYS REV B, V32, P5532, DOI 10.1103/PhysRevB.32.5532 MARKELZ AG, 1994, SOLID STATE ELECTRON, V37, P1243, DOI 10.1016/0038-1101(94)90399-9 MARKELZ AG, 1995, THESIS U CALIFORNIA SHAH J, 1984, APPL PHYS LETT, V44, P322, DOI 10.1063/1.94739 SHAH J, 1978, SOLID STATE ELECTRON, V21, P43, DOI 10.1016/0038-1101(78)90113-2 YANG CH, 1985, PHYS REV LETT, V55, P2359, DOI 10.1103/PhysRevLett.55.2359 Asmar, NG Cerne, J Markelz, AG Gwinn, EG Sherwin, MS Campman, KL Gossard, AC Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 59 7 Amer inst physics Woodbury
Keywords: hot-electrons; Physics

Undressing a collective intersubband excitation in a quantum well - Craig, K.; Galdrikian, B.; Heyman, J. N.; Markelz, A. G.; Williams, J. B.; Sherwin, M. S.; Campman, K.; Hopkins, P. F.; Gossard, A. C. (Physical Review Letters, 1996)
We have experimentally measured the 1-2 intersubband absorption in a single 40 nm wide modulation-doped Al0.3Ga0.7As/GaAs square quantum well as a function of frequency, intensity, and charge density. The low-intensity depolarization-shifted absorption occurs near 80 cm(-1) (10 meV or 2.4 THz), nearly 30% higher than the intersubband spacing. At higher intensities, the absorption peak shifts to lower frequencies. Our data are in good agreement with a theory proposed by Zaluzny, which attributes the redshift to a reduction in the depolarization shift as the excited subband becomes populated.
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 78

NONLINEAR QUANTUM DYNAMICS IN SEMICONDUCTOR QUANTUM-WELLS - Sherwin, M. S.; Craig, K.; Galdrikian, B.; Heyman, J.; Markelz, A.; Campman, K.; Fafard, S.; Hopkins, P. F.; Gossard, A. (Physica D-Nonlinear Phenomena, 1995)
We discuss recent measurements of the nonlinear response of electrons in wide quantum wells driven by intense electromagnetic radiation at terahertz frequencies. The theme is the interplay of quantum mechanics, strong periodic driving, the electron-electron interaction and dissipation. We discuss harmonic generation from an asymmetric double quantum well in which the effects of dynamic screening are important. Measurements and theory are found to be in good agreement. We also discuss intensity-dependent absorption in a 400 Angstrom square quantum well. A new nonlinear quantum effect occurs, in which the frequency at which electromagnetic radiation is absorbed shifts to the red with increasing intensity. The preliminary experimental results are in agreement with a theory by Zaluzny, in which the source of the nonlinearity is the self-consistent potential in the Hartree approximation for the electron dynamics.
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 14th Annual International Conference of the Center-for-Nonlinear-Studies - Quantum Complexity in Mesoscopic Systems May 16-20, 1994 Los alamos, nm Ctr nonlinear studies 34

QUENCHING OF EXCITONIC QUANTUM-WELL PHOTOLUMINESCENCE BY INTENSE FAR-INFRARED RADIATION - FREE-CARRIER HEATING - Cerne, J.; Markelz, A. G.; Sherwin, M. S.; Allen, S. J.; Sundaram, M.; Gossard, A. C.; Vanson, P. C.; Bimberg, D. (Physical Review B, 1995)
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 29

RESONANT-ENERGY RELAXATION OF TERAHERTZ-DRIVEN 2-DIMENSIONAL ELECTRON GASES - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Cerne, J.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Physical Review B, 1995)
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 119

Far-infrared harmonic generation from semiconductor heterostructures - Markelz, A.G.; Gwinn, E. G.; Sherwin, M. S.; Heyman, J. N.; Nguyen, C.; Kroemer, H. (SPIE Proceedings, 1994)

FAR-INFRARED SATURATION SPECTROSCOPY OF A SINGLE SQUARE-WELL - Craig, K.; Felix, C. L.; Heyman, J. N.; Markelz, A. G.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Semiconductor Science and Technology, 1994)
We have performed saturation spectroscopy measurements of the lowest intersubband transition in a single 400 angstrom GaAs/Al0.3Ga0.7As modulation-doped square quantum well. We couple intense tunable far-infrared radiation from the Santa Barbara free electron laser into our sample using an edge-coupling technique and measure absorption as a function of frequency and intensity. Saturation and frequency shifts in the absorption line are clearly observed. We attribute the frequency shifts to reductions in the many-body depolarization shift. From our preliminary measurements, we estimate the intersubband relaxation time to be 600 ps to within a factor of three.
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 S 8th International Conference on Hot Carriers in Semiconductors Aug 16-20, 1993 Oxford univ, oxford, england Sci & engn res council; royal soc; brit council; oxford univ 31

GIANT 3RD-ORDER NONLINEAR SUSCEPTIBILITIES FOR INPLANE FAR-INFRARED EXCITATION OF SINGLE INAS QUANTUM-WELLS - Markelz, A. G.; Gwinn, E. G.; Sherwin, M. S.; Nguyen, C.; Kroemer, H. (Solid-State Electronics, 1994)
Third-order, free-carrier nonlinear susceptibilities, chi(3), have been measured between 19 and 23 cm-1 for three InAs/AlSb quantum wells with sheet densities between 2.5 x 10(12) cm-2 and 8 x 10(12) cm-2. We find that these wells are strongly nonlinear at far-infrared frequencies: odd harmonics ninth order have been observed at high incident intensities, and the peak value of chi(3) reaches approximately 1 esu. This is several orders of magnitude larger than previously reported values for chi(3) in bulk n-GaAs (10(-4) esu)[1] and in polyacetylene (10(-7) esu)[2]. The large magnitude of chi(3) is attributed to the high carrier density in the InAs wells, and to the strong non-parabolicity of the conduction band in InAs. However, the free-carrier chi(3) for bulk InAs predicts a density-dependence different from that observed, and the measured decrease in chi(3) with increasing intensity indicates non-perturbative response. We find that the anisotropy of chi(3) displays the expected 4-fold symmetry.
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 6th International Conference on Modulated Semiconductor Structures Aug 23-27, 1993 Garmisch partenkir, germany Tech univ munchen, walter schottky inst 9

PROBING TERAHERTZ DYNAMICS IN SEMICONDUCTOR NANOSTRUCTURES WITH UCSB FREE-ELECTRON LASERS - Allen, S. J.; Craig, K.; Felix, C. L.; Guimaraes, P.; Heyman, J. N.; Kaminski, J. P.; Keay, B. J.; Markelz, A. G.; Ramian, G.; Scott, J. S.; Sherwin, M. S.; Campman, K. L.; et al. (Journal of Luminescence, 1994)
The UCSB free-electron lasers provide kilowatts of continuously tunable radiation from 120 GHz to 4.8 THz. They have the most impact on terahertz science and technology that require a tunable, high power source to explore non-linear dynamics or that sacrifice incident power to recover the linear response of systems with very small cross-section. We describe three experiments that demonstrate the utility of these lasers in experiments on the terahertz dynamics of semiconductor nanostructures: (i) terahertz dynamics of resonant tunneling diodes, (ii) saturation spectroscopy of quantum wells and (iii) photon-assisted tunneling in superlattices.
Sherwin, Mark S/Q-4762-2017; Guimaraes, Paulo Sergio Soares/B-6918-2012 Sherwin, Mark S/0000-0002-3869-1893; Guimaraes, Paulo Sergio Soares/0000-0002-0113-2641; Markelz, Andrea/0000-0003-0443-4319 1993 International Conference on Luminescence (ICL 93) Aug 09-13, 1993 Univ connecticut, storrs, ct Univ connecticut; opt soc amer; amer phys soc; ieee, laser & electro opt soc; int union pure & appl phys; int sci fdn; univ connecticut res fdn 3

SUBCUBIC POWER DEPENDENCE OF 3RD-HARMONIC GENERATION FOR INPLANE, FAR-INFRARED EXCITATION OF INAS QUANTUM-WELLS - Markelz, A. G.; Asmar, N. G.; Gwinn, E. G.; Sherwin, M. S.; Nguyen, C.; Kroemer, H. (Semiconductor Science and Technology, 1994)
Large third-order, free-carrier nonlinear susceptibilities, chi(3) (to approximately 0.2 esu), and subcubic dependence of the third-harmonic power on the incident intensity, have been observed between 19 cm-1 and 23 cm-1 for InAs/AlSb quantum wells with electron sheet densities between 2.5 x 10(12) cm-2 and 8 X 10(12) cm-2. We find that the transmission of the fundamental, and the samples' DC conductivity, decrease with increasing incident intensity, indicating a large rise in the scattering rate. Using the intensity-dependent transmission to account for absorption in the sample is not sufficient to recover a cubic power law for the third-harmonic intensity. In addition, given the increased scattering rate indicated by the conductivity data, the bulk free-carrier chi(3) due to non-parabolicity should decrease dramatically with increasing fundamental intensity, contrary to our results. Thus, non-parabolicity alone cannot account for the observed third-harmonic response.
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 S 8th International Conference on Hot Carriers in Semiconductors Aug 16-20, 1993 Oxford univ, oxford, england Sci & engn res council; royal soc; brit council; oxford univ 4

Far-infrared nonlinear response of electrons in semiconductor nanostructures - Sherwin, M. S.; Asmar, N. G.; Bewley, W. W.; Craig, K.; Felix, C. L.; Galdrikian, B.; Gwinn, E. G.; Markelz, A.G.; Gossard, A. C.; Hopkins, P. F.; Sundaram, M.; Birnir, B. (SPIE Proceedings, 1993)

8 NEW HIGH-TEMPERATURE SUPERCONDUCTORS WITH THE 1-2-4 STRUCTURE - Morris, D. E.; Nickel, J. H.; Wei, J. Y. T.; Asmar, N. G.; Scott, J. S.; Scheven, U. M.; Hultgren, C. T.; Markelz, A. G.; Post, J. E.; Heaney, P. J.; Veblen, D. R.; Hazen, R. M. (Physical Review B, 1989)
Scheven, Ulrich/D-7582-2013 Markelz, Andrea/0000-0003-0443-4319; Scheven, Ulrich/0000-0001-8111-0081 B 241